Treatment of Radius Aneurysmal Bone Cyst with Fibular Autograft: A Case Report - Serbest, Sancar; Kaya, Erdal; Gökçe, Halil (Fırat University, 2012)
Aneurysmal bone cyst is a benign expansile bone lesion that mainly affects children and young adults. Despite its benign name, some of these lesions have a remarkable ability to destroy bone and grow rapidly. Treatment options of aneurysmal bone cysts include complete resection, curettage, curet-tage with bone grafting, selective arterial embolization (as a primary treatment or preoperative adjuvant therapy), and percutaneous injection of fibrosing agent. When possible complete excision is the treatment of choice. We present case of radius aneurysmal bone cysts successfully treated with bone defects after resection of tumors are commonly reconstructed with the use of nonvascularized fibular autograft and internal fixation

Anevrizmal kemik kisti, iyi huylu, genişleme özelliği olan ve daha çok çocuk ve gençlerde görülen kemik lezyonlarıdır. İyi huylu olmalarına karşın, bu lezyonlardan bazıları hızlı büyüme ve kemikte harabiyet yapma yeteneğine sahiptirler. Tedavi seçenekleri arasında tam rezeksiyon, küretaj, kemik greftleme ile küretaj, selektif arteryel embolizasyon (primer tedavi olarak veya preoperatif terapi) ve perkütan fibrozan ajan enjeksiyonu sayılabilir. Anevrizmal kemik kistinin tedavisinde tam çıkarma en iyi yöntemdir. Bu bildiride, radius anevrizmal kemik kisti olan ve tümör rezeksiyonu sonrası meydana gelen kemik defektinin vaskülarize olmayan otolog fibula grefti ve internal fiksasyon ile başarılı şekilde tedavi edilmiş bir olguyu sunmaktayız..
Radius Anevrizmal Kemik Kistinin Otolog Fibula Grefti ile Tedavisi: Olgu Sunumu